Діалог з Іншим крізь призму екзистенційного досвіду автора у сучасній українській поезії (Сергій Жадан "Життя Марії") - Тичініна, Альона Романівна (Uniwersytet w Siedlcach, 2024)
Relying on the methodologies of M. Bakhtin, M. Buber, P. Ricœur, and W. Schmid, the article under studies analyzes Serhiy Zhadan’s collection The Life of Mary (2015). It points out that various (post)-traumatic autobiographic existentials, caused by war and revealed in poetic narratives (freedom, hatred, fear, understanding, love, nostalgia, guilt, injustice, death), provoke a dialogue with “the Other”, which may be implemented at a few levels. Firstly, the book by Zhadan has a double intertextual frame – the poetry by Rainer Maria Rilke and Czesław Miłosz. Secondly, the textual imitations of dialogic structure in the collection do not only reveal lyrical images and emotions, but also present stories and events through modeling different ways of conducting a conversation, dialogue, and storytelling, in particular through the use of zeugma, direct and indirect speech, retelling, and appeals to „the Other”. The third level outlines the dialogue with characters, including transitory sacred images (Mary, Jesus, Magdalene, Thomas), as well as people of different social groups. A dialogue with the reader is exercised through paratext, which is an eloquent hermeneutical key; through the intellectual game of the author and the reader in the course of decoding the meta-logical series; through direct appeals to the recipient, imperative constructions that model the process of storytelling.
Keywords: dialogue; narrative; existentiells; Serhiy Zhadan; poetic text; metaphor